Commonwealth place‐based policies for addressing geographically concentrated disadvantage: A typology and critical analysis. Issue 1 (10th June 2021) - Hart, Aaron; Connolly, Julie
Abstract: A suite of 'place‐based' Commonwealth policy frameworks to address geographically concentrated socio‐economic disadvantage foreground local knowledge and devolve some decisions to multi‐government and local agent governance bodies. We analyse these policies with reference to Dewey's theory of democratic experimentalism, focussing on how publics are constituted in place and enrolled in processes of deliberation and problematisation, and on how policy success is framed. We categorise 'place‐based' policies into three groups. Statutory collaboration policies enable coordinated intergovernmental investment in regional economic regeneration and enact broad publics through a concern with economic growth. Collective impact policies commission for social service integration and figure the users and providers of social services as their publics. Indigenous partnership policies are concerned with 'self‐reliance', economic participation, and empowerment among Indigenous people. We find that only the policies in the latter type clearly provide their publics with epistemic or decision‐making power. Further research on the implementation of collective impact policies would be necessary to determine their participatory scope, and statutory collaboration policies provide little opportunity for input from their publics. Our aim is to highlight the democratic significance of who is included in place‐based deliberations and what is deemed to be valuable. Abstract : We propose a typology of 'place‐based' Commonwealth policy frameworks to address geographically concentrated socioeconomic disadvantage. We also analyse these policies with reference to Dewey's theory of democratic experimentalism, focussing on how publics are constituted in place and enrolled in processes of deliberation and problematisation; and on how success is framed.